Emotion and culture of eye-metaphors in Mandarin, Spanish and German - Ching-yu Hsieh 謝菁玉, Shelley; Lu 盧慧娟, Hui-chuan (Círculo de Lingüística Aplicada a la Comunicación, 2014)
This study attempts to give a cognitive semantic study of eye expressions (EEs) in Chinese, Spanish and German. The majority of the data are collected from corpora and dictionaries. The research questions are: (1) Is the BODY IS STATIC hypothesis proposed by Hsieh and Lu (2012) valid? (2) Do the verbs in EEs showing emotions suggest something? And, (3) what cultural aspects do the EEs in three languages involve? The results show that the analysis of semantic molecules and tenors of the EEs confirm the validity of BODY IS STATIC hypothesis. The verbs of the EEs play an important role in expressing emotion. The verbs that are inherited for other body parts, such as for hand, mouth, are extended to the sight domain and assist such emotion communication effectively. Bodily experiences work in linguistic as a whole as well. Finally, cultural aspects of social behavior and social communication in the specific social groups are shown. They are all revealed through a cross-cultural linguistic comparison.